Genomic correlates of response to immune checkpoint therapies in clear cell renal cell carcinoma - Miao, Diana; Margolis, Claire A.; Gao, Wenhua; Voss, Martin H.; Li, Wei; Martini, Dylan J.; Norton, Craig; Bossé, Dominick; Wankowicz, Stephanie M.; Cullen, Dana; Horak, Christine; Wind-Rotolo, Megan; et al. (Science (American Association for the Advancement of Science), 2018)
Immune checkpoint inhibitors induce durable tumor regressions in some, but not all, cancer patients. Understanding the mechanisms that determine tumor sensitivity to these drugs could potentially expand the number of patients who benefit (see the Perspective by Ghorani and Quezada). Pan et al. discovered that tumor cells in which a specific SWI/SNF chromatin remodeling complex had been experimentally inactivated were more sensitive to T cell–mediated killing. The cells were more responsive to interferon-γ, leading to increased secretion of cytokines that promote antitumor immunity. Miao et al. examined the genomic features of tumors from patients with metastatic renal cell carcinoma who had been treated with immune checkpoint inhibitors. Tumors harboring inactivating mutations in PBRM1 , which encodes a subunit of the same SWI/SNF complex, were more likely to respond to the drugs. Science , this issue p. 770 , p. 801 ; see also p. 745 Renal cell cancers with mutations in a specific chromatin regulator have a better clinical response to immunotherapy. Immune checkpoint inhibitors targeting the programmed cell death 1 receptor (PD-1) improve survival in a subset of patients with clear cell renal cell carcinoma (ccRCC). To identify genomic alterations in ccRCC that correlate with response to anti–PD-1 monotherapy, we performed whole-exome sequencing of metastatic ccRCC from 35 patients. We found that clinical benefit was associated with loss-of-function mutations in the PBRM1 gene ( P = 0.012), which encodes a subunit of the PBAF switch-sucrose nonfermentable (SWI/SNF) chromatin remodeling complex. We confirmed this finding in an independent validation cohort of 63 ccRCC patients treated with PD-1 or PD-L1 (PD-1 ligand) blockade therapy alone or in combination with anti–CTLA-4 (cytotoxic T lymphocyte-associated protein 4) therapies ( P = 0.0071). Gene-expression analysis of PBAF-deficient ccRCC cell lines and PBRM1 -deficient tumors revealed altered transcriptional output in JAK-STAT (Janus kinase–signal transducers and activators of transcription), hypoxia, and immune signaling pathways. PBRM1 loss in ccRCC may alter global tumor-cell expression profiles to influence responsiveness to immune checkpoint therapy.